Impact assessment of various scenarios of Doha Agenda on West and Central Africa cotton sectors - (:unkn) unknown (My University, 2011)
Agriculture, especially cotton, causes contention in the World Trade Organization’s (WTO) Doha Development Agenda (DDA) since 2001. This study analyses and provides quantitative estimates of the likely economics impacts of various scenarios. We propose an alternative scenario further based on the principle of special and differential treatment provided to developing countries. We consider seven key scenarios in this study: (1) the Uruguay Round agreements, (2) Falconer' negotiation draft, revised in December 2008 but without special measures for cotton, (3) Similar Falconer's draft but including special measures for cotton as proposed by the C4 Group, (4) the European Union position, (5) the United States position, (6) our alternative scenario of agreements and (7) the total liberalization even if ambitious in scope. Our alternative scenario lies on the improvement of the access of African cotton into the Chinese market and on the strengthening of domestic support to cotton production in West and Central Africa. This scenario is original by considering the set up of a new fund for international solidarity through the subsidy savings implemented by developed countries. We use the Agricultural trade Policy Simulation Model (ATPSM) to evaluate the economic effect and the Stiglitz and Charlton theory of equity for equity assessment. The results showed that our alternative scenario increases the world cotton price by 8.1%, the producer price by 10.8% which is higher than the Falconer' negotiation draft with special measures for cotton (9.0%) and the United States position (6.1%). With regard to the equity criteria, our alternative scenario is as attractive as the other scenarios in comparison with the Uruguay Round agreements scenario. The alternative scenario can help to conclude the WTO-Doha Development Agenda. This scenario takes into account some key elements of a compromise between major actors of WTO, and provides provisions for and international fu
Keywords: African Research